Substance use instruments for refugees-systematic review. (20th October 2021) - Marth, S; Jakubauskiene, M; Schäfer, Ingo; Lindert, J
Abstract: Background: Substance use is a problem among refugee populations. Instruments which assess substance use have been translated into different languages, but are not culturally sensitive. This research gap has to be filled to acquire information about substance use disorders in refugee populations, especially from Arabic countries, as a confession to using substances in those countries is culturally problematic. Methods: Following databases were systematically searched: EMBASE, PubMed, CINAHL, Web of Sciences and PsychInfo resulting in 2659 hits. After removing 5 duplicates, 2650 studies were screened. After exclusion of irrelevant studies, 264 studies were assessed for eligibility and 128 studies were, so far included. Inclusion criteria were original studies, migrant or refugee participants, minimum age 18 years, usage of quantitative measures and substance use as the outcome. A data extraction sheet was developed with three reviewers working on it. Results: 49 studies were found to use validated instruments. Most frequently used was the AUDIT (n = 17), followed by the WMH-CIDI (n = 11) and the CAGE questionnaire (n = 9). The majority of the studies (n = 55) used self-developed instrument with few items. To our knowledge, no study used a culturally sensitive adapted questionnaire. Conclusions: More studies used self-developed items for assessing substance use than validated instruments. None of the studies used a culturally sensitive adapted instrument. This is a clear indication that such an instrument is needed for research and treatment. With a culturally sensitive instrument, the care for refugees and migrants could be improved and adjusted, possibly resulting in better public health outcomes. Main messages: As refugee populations continue to grow, an adequate screening instrument for substance abuse/dependence for these individuals is missing. With the development of a culturally sensitive instrument, identification and treatment of refugees and migrants can be improved.